Nur Seri Oil Palm Nursery - Osman, Mohammad Syahfiq; Onsang, Nordin; Damrih, Saprudin; Abdul Malik, Rozaini; Pirman, Shariel Mohd Saifullah (2013)
The name of our company is Nur Seri Oil Palm Nursery. Oil palm nursery is a business that the oil palm will comes into maturity at 12 months or earlier from field planting, with peak yield realized at third or more years thereafter. Our main office is located at Lahad Datu, Sabah together with our nursery ; we expect to start up our business on April 2014. With the reference of government of Sabah there are 3.12 million people in Sabah. On the other hand based on the scientific research demand for oil palm will increase every day and the seed will be develop in quality in time from time so, we are taking this opportunity to start a business related to the oil palm services. The future prospects of our business are people around Sabah and at the same time aiming the international tourist. This is because, by referring the statistic of world oil palm statistic, Malaysia is the first country in production of oil palm. On the oth er hand, we can aim for the international customer in supplying the oil palm budding. This business has a high potential to expand in a long term business. In order to make this project happen we are requires funding's RM 129,796 to start the business. We are prospecting to increase 5% and 10% sales of our business on third and fourth year respectively.